THE MATTER PERTAINING TO THE POSTMODERN TOURIST PRODUCTS REPRESENTING THE AREA OF THE OLD CITY OF JAKARTA - Entas, Derinta; Mudana, I Gede (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2018)
Cultural representation from the perspective of cultural studies is the concept of production, mediation, and reception. The common people know it as production, distribution, and consumption. The main topic of the present study is the appearance of the past in its current form. The appearance of the past using the cultural capital of the area is raised and packaged with new forms and meanings. The study focuses on the forms of the postmodern tourist products which represent the area of the Old City of Jakarta. The study uses the qualitative method in which the forms of the postmodern tourist products representing the area of the Old City of Jakarta are simply analyzed. The data were collected through observation, interview, documentation, and questionnaire. The data were analyzed interpretatively using the theory of cultural representation. The result of the study shows that the postmodern tourist products represent the area of the Old City of Jakarta in the forms of the production process, distribution process, and consumption process. They all strengthen the forms of the postmodern tourism products representing the area of the Old City of Jakarta. The products include City Tour, Heritage Trails; Junior Heritage Trails: Fun Learning in History; Sunda Kelapa Cycling Tour; Kampung Arab Cycling Tour; Marine Tourism (Wisata Bahari): Sunda Kelapa Harbour and Onrust Island; Jakarta Heritage Trails: Free Old City Tour; Chinatown Journey Experience Through The Eyes of History; Old City Adventure (Kelana Kota Tua); Going Along the Fortress of Batavia City; Jakarta Urban Legend Tour; Past Time Trip (Plesiran Tempoe Doeloe). The different tourist products have been created by the tourism agents, and are packaged in such a way starting from historical facts to mythological stories that they all have enriched the tourist attractions in the Old City of Jakarta.